2023
DOI: 10.2147/jir.s397837
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Inflammatory Mediators and Bone Outcomes in Postmenopausal Women: A Cross-Sectional Analysis of Baseline Data from the Prune Study

Abstract: Purpose Hypoestrogenism triggers increased production of inflammatory mediators, which contribute to bone loss during postmenopausal osteoporosis. This study aimed to investigate the association between circulating inflammatory markers and bone outcomes in postmenopausal women. Materials and methods We conducted a cross-sectional, secondary analysis of baseline data from participants who completed a 12-month randomized controlled trial, The Prune Study (NCT02822378), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…As a member of the chemokine family, HMGB1 induces the softening and relaxation of internal cervical ori ce by recruiting the downstream complement or chemokine C3a; low HMGB1 level can recruit the immune cells and promote the proliferation and differentiation of endometrial stromal cells required for normal pregnancy, while high HMGB1 level is associated with pregnancy failure [13][14] . sTNFR-1 is a member of the TNFR family, whose regulatory effects on different TNF-α receptors can enhance the pathological role of in ammatory factors, intensifying their damage to amniotic sac wall cells to increase the risk of premature delivery [15][16] . NLR is a sensitive in ammatory index discovered in current research, which not only indicates the role of neutrophils in infection, but also correlates with the lymphocyte count in the body.…”
Section: Research Results Analysismentioning
confidence: 99%
“…As a member of the chemokine family, HMGB1 induces the softening and relaxation of internal cervical ori ce by recruiting the downstream complement or chemokine C3a; low HMGB1 level can recruit the immune cells and promote the proliferation and differentiation of endometrial stromal cells required for normal pregnancy, while high HMGB1 level is associated with pregnancy failure [13][14] . sTNFR-1 is a member of the TNFR family, whose regulatory effects on different TNF-α receptors can enhance the pathological role of in ammatory factors, intensifying their damage to amniotic sac wall cells to increase the risk of premature delivery [15][16] . NLR is a sensitive in ammatory index discovered in current research, which not only indicates the role of neutrophils in infection, but also correlates with the lymphocyte count in the body.…”
Section: Research Results Analysismentioning
confidence: 99%
“…Without estrogen, more dendritic cells were shown to express IL-7 and IL-15, which upregulates IL-17 and TNF-α production by T cells (Saxena et al, 2021). Furthermore, a cross-sectional clinical study of postmenopausal women showed that elevated inflammatory markers such as IL-6, IL-β, and TNF-α were negatively correlated with bone mass (Damani et al, 2023). These findings indicate estrogen regulates bone remodeling through immune-mediated effects and direct signaling within the bone microenvironment.…”
Section: Frontiers In Systems Biologymentioning
confidence: 99%
“…Based on their study, Damani et al 1 suggest that post-menopausal osteoporosis is due to enhanced production of inflammatory cytokines. Osteoporosis seen in inflammatory conditions such as rheumatoid arthritis is due to excess production of IL-6, TNF-α, and other inflammatory cytokines.…”
Section: Dear Editormentioning
confidence: 99%